Microbial Alkalinity Production and Silicate Alteration in Methane Charged Marine Sediments: Implications for Porewater Chemistry and Diagenetic Carbonate Formation - Meister, Patrick; Herda, Gerhard; Petrishcheva, Elena; Gier, Susanne; Dickens, Gerald R.; Bauer, Christian; Liu, Bo (Frontiers in Earth Science, 2022)
A numerical reaction-transport model was developed to simulate the effects of microbial activity and mineral reactions on the composition of porewater in a 230-m-thick Pleistocene interval drilled in the Peru-Chile Trench (Ocean Drilling Program, Site 1230). This site has porewater profiles similar to those along many continental margins, where intense methanogenesis occurs and alkalinity surpasses 100 mmol/l. Simulations show that microbial sulphate reduction, anaerobic oxidation of methane, and ammonium release from organic matter degradation only account for parts of the total alkalinity, and the excess CO2 produced during methanogenesis leads to acidification of the porewater. Additional alkalinity is produced by slow alteration of primary aluminosilicate minerals to kaolinite and SiO2. Overall, alkalinity production in the methanogenic zones is sufficient to prevent dissolution of carbonate minerals; indeed, it contributes to induce the formation of cemented carbonate layers at a supersaturation front near the sulphate-methane transition zone. Within the methanogenic zone, carbonate formation is largely inhibited by cation diffusion but occurs rapidly if cations are transported into the zone via tectonic faults. The simulation presented here provides fundamental insight into the diagenetic effects of the deep biosphere and may also be applicable for the long-term prediction of the stability and safety of deep CO2 storage reservoirs.